Impact of insecticides and botanicals on leaf folder and stem borer in the mid hill rainfed rice agroecosystem - Vinothkumar, B (Indian Journal of Plant Protection, 2020)
Studies were conducted to evaluate the new molecular insecticides and botanicals as foliar application for its bioefficacy against leaf folders, stem borer and toxicity against predators of mid hill rain fed rice at Hybrid Rice Evaluation Centre, Tamil Nadu Agricultural University, Gudalur during 2010-2012. Among nine treatments, flubendiamide @ 24 g. a.i. ha-1, rynaxypyr @ 30 g. a.i. ha-1, fipronil @ 50 g. a.i. ha-1 were significantly superior to other treatments with more than 95 per cent reduction of leaf folder and stem borer damage over untreated control. Triazophos @ 400 g. a.i. ha-1, chlorpyriphos @ 250 g. a.i. ha-1, quinalphos @ 250 g. a.i. ha-1 recorded more than 70 per cent reduction of leaf folder and stem borer damage over untreated control. Botanicals such as Eupatorium adinophorum leaf extract @ 5 % and NSKE @ 5 % were less effective than insecticides. The results of the three season trials revealed that all the insecticides were harmful to the population of spiders, coccinellids and rove beetles than botanicals. The order of relative safety to natural enemies based on the per cent reduction over control were, E. adinophorum leaf extract @ 5 % = NSKE @ 5 % > chlorpyriphos @ 250 g. a.i. ha-1 = quinalphos @ 250 g. a.i. ha-1 > rynaxypyr @ 30 g. a.i. ha-1 = fipronil @ 50 g. a.i. ha-1 = flubendiamide @ 24 g. a.i. ha-1 > triazophos @ 400 g. a.i. ha-1.